Thermal stability, structural and optical properties of rice husk sillica borotellurite glasses containing MnO2 - Ismail, Zaitizila; Mohamed Kamari, Halimah; Muhammad, Farah Diana; Mohd Shah, Nurisya; Mohd Zaid, Mohd Hafiz (National Institute of Materials Physics, National Institute of Optoelectronics, 2018)
The quaternary glass system {[(TeO2)0.7(B2O3)0.3]0.8[SiO2]0.2}1-xMnO2x where x = 0.00, 0.01, 0.02, 0.03, 0.04 and 0.05 molar fraction was prepared by melt quenching technique. The amorphous nature of the glass is confirmed by X-ray diffraction patterns and Scanning Electron Microscopy(SEM). The prepared glass samples had also been characterized by Differential Scanning Calorimetry(DSC). The glass transition(Tg), onset glass transition(To), crystallization(Tc) and melting temperature(Tm) values were measured from DSC thermo-gram. Results from DSC indicate good thermal stability and low value of fragility (F) of the prepared glass samples. Thermal stability(Ts), Hurby parameter(Kgl), fragility(F) and activation energy(Ea) were calculated for every glass composition. It is observed that the optical band gap decreases with the concentration of MnO2. On the other hand, the refractive index(n) is observed to increase as the concentration of MnO2 increases. Fourier Transform Infrared (FTIR) spectroscopy has been done to identify the functional group in glass sample.